Outcome and Structural Integrity of Rotator Cuff after Arthroscopic Treatment of Large and Massive Tears with Double Row Technique: A 2-Year Followup - Ignacio Carbonel; Angel A. Martínez; Elisa Aldea; Jorge Ripalda; Antonio Herrera (Advances in Orthopedics)
Purpose. The purpose of this study was to evaluate the functional outcome and the tendon healing after arthroscopic double row rotator cuff repair of large and massive rotator cuff tears. Methods. 82 patients with a full-thickness large and massive rotator cuff tear underwent arthroscopic repair with double row technique. Results were evaluated by use of the UCLA, ASES, and Constant questionnaires, the Shoulder Strength Index (SSI), and range of motion. Follow-up time was 2 years. Magnetic resonance imaging (MRI) studies were performed on each shoulder preoperatively and 2 years after repair. Results. 100% of the patients were followed up. UCLA, ASES, and Constant questionnaires showed significant improvement compared with preoperatively (P<0.001). Range of motion and SSI in flexion, abduction, and internal and external rotation also showed significant improvement (P<0.001). MRI studies showed 24 cases of tear after repair (29%). Only 8 cases were a full-thickness tear. Conclusions. At two years of followup, in large and massive rotator cuff tears, an arthroscopic double row rotator cuff repair technique produces an excellent functional outcome and structural integrity.